The Evolution of University Chancellorship in Kenya - Munene, Ishmael (International Higher Education, 2020)
At Kenyan public universities, the chancellor is a ceremonial position. Yet, there is an expectation that chancellors will steer universities in specific directions. The sociopolitical context of the evolution of the chancellorship in Kenya shows that there are contextual limits to the success of chancellors in transforming their universities.